CARBOHYDRATE METABOLISM AND HYPOGLYCEMIA RISK IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AND ISCHEMIC CEREBROVASCULAR DISEASES - K. V. Antonova; M. М. Tanashyan; T. I. Romantsova; О. V. Lagoda; A. A. Shabalina (Медицинский совет, 2017)
In patients with Type 2 diabetes mellitus 2 (DM2) the active course of atherosclerosis, increased risk of stroke and cognitive impairment are observed. The cerebrovascular or neurodegenerative disorders, metabolic disorders, hypoglycemic episodes can play the part in the development of cognitive impairment.Objective: to evaluate carbohydrate metabolism and identification of hypoglycemic conditions for patients with T2DM and ischemic cerebrovascular disease.Materials and methods. 99 patients were studied, among them 46 (46.5 per cent) men and 53 (53,5%) women, average age 64 ± 8.3 years. Of these 46 patients with dyscirculatory encephalopathy (DE) and 53 with a history of ischemic stroke.Results. Patients showed cognitive changes. All patients had evidence of atherosclerosis of the main arteries of the head, signicant stenoses were observed in 42.4 per cent, and multiple atherosclerotic changes – 39.4% of the patients. The T2DM disease duration was 8.4 ± 6 years, HbA1c – a 7.8 ± 1.9 percent. Hypoglycemia is marked on the background antidiabetic therapy in 15% of patients, 7 of them are unrecognizable. In patients with hypogycemic episodes of disease duration and frequency of reduced GFR was significantly higher. Conclusions. Ischemic cerebrovascular disease in DM2 patients takes place on the background of atherosclerosis of the main arteries of the head, hypertension, renal dysfunction and are accompanied by the risk of iatrogenic hypoglycemia. Hypoglycemic states often develop with increasing duration of the disease of type 2 diabetes and reduction of the glomerular filtration rate. It is recommendable to regularly control blood glucose to reduce the risk of hypoglycemic conditions.